A EMÛNÂ EM HAB 2:4b: ASPECTOS SEMÂNTICOS - Caldas Moura, Ozeas (Revista Hermenêutica (descontinuada), 2004)
RESUMO O vocábulo hebraico emûnâ, derivado do verbo aman podeser traduzido como “fi delidade” (seguindo-se da idéia de Niphal)em 48 das 49 vezes em que aparece na Bíblia Hebraica. A exceçãofi caria por conta de uso em Hab. 2:4b. Nessa passagem de Habacuc,tendo em vista que o contexto profético da perícope onde o vocábuloaparece (o oráculo de Yhwh em 2, 1-5 sobre o fi m do arrogante epromessa de vida para o justo), bem como o contexto de todo o livrodesse profeta (Deus controla os eventos da História e os direcionapara o bem do justo) deveria emûnâ ser melhor compreendida como“fé / confi ança” em Deus e em Suas promessas (seguindo-se a idéiade Hiphil de !aman, onde esse verbo aparece várias vezes no AntigoTestamento num contexto de oráculos divinos com o signifi cado de“crer”, “ter fé”, “confi ar”). ABSTRACT The word hebrew !emûnâ , derived of the verb !aman can betranslated as “fi delity” (being followed the idea of Niphal) in 48 of the49 times in that appears in the Hebrew Bible. The exception wouldbe due to its use in Hab 2:4b. In that passage of Habacuc, tends inview the prophetic context of the periscope where the word appears(the oracle of Yhwh in 2, 1-5 on the end of the arrogant and lifepromise for the just), as well as the context of whole that prophet’sbook (God controls the events of the History and it addresses themfor the good of the just) it would owe ! emûnâ to be understood betteras “faith / trust” in God and in its promises (being followed the ideaof Hiphil of !aman, where that verb appears several times in theOld Testament in a context of divine oracles with the meaning of“believing”, “to have faith”, “to trust”).